Novel, laboratory-independent device to measure extracellular enzymatic activity in soils - Fetzer, Jasmin; Meller, Sonia; Iven, Hélène; Baur, Denise; García Rivera, Paula; Meller, Alan; Luster, Jörg (Frontiers in Environmental Science, 2025)
Here we introduce a novel laboratory-independent Soil Enzymatic Activity Reader (SEAR). The assessment of extracellular enzymatic activity is based on the reaction of enzymes in a reactive layer of homogenized soil with fluorogenic substrates upon contact with an agarose gel in which they are dissolved. The reaction products are detected on the opposite side of the transparent gel by their fluorescence. Reaction plates with multiple gel compartments allow for the simultaneous assessment of several enzymes, including analytical replicates and suitable controls. We validated the new method by using sand, spiked with solutions of increasing concentrations of different enzymes. We further constrained the boundary conditions of operation, including limits of rate detection, precision, and the ranges of substrate concentrations, soil properties, and environmental conditions. We found our method to operate well for a wide range of different soils, comprising textures from sand to silty clay loam, acid forest soils with pH < 4 to carbonate containing agricultural soils, and soil organic carbon contents up to 18%. Furthermore, by successfully testing soil moistures from 2% to 173% of the respective water holding capacity and temperatures from 6 °C to 50 °C, we could show that measurements are possible under most conditions encountered in the field. We conclude that with SEAR, a novel device is available that allows fast, easy, and standardized measurements of extracellular enzymatic activity close to field conditions without laboratory access and thus without the need for storage and related sample pretreatments that may affect the results.